Peran Status dan Modal Sosial dalam Penyembuhan dari Covid-19 - Paulus Dwintarto (Seri Filsafat Teologi, 2021)
In this article, the author reflects on his experience as a survivor of COVID-19, employing a sociological concept, namely social capital. The author was infected with the covid-19 virus while studying, precisely while working on his thesis, at St. John's University, New York. Suffering from illness, in this case due to COVID-19, in a foreign country was already a difficult experience. The situation was even worse because at that time, medical personnel in the United States did not have adequate and reliable knowledge in dealing with COVID-19 since the pandemic had just entered the first wave. The author experienced the difficulty of getting access to hospital care because of the surge in the number of patients. The author recognized that his social status as a Catholic priest was an invaluable social capital in the process of his care and recovery from illness, such as enabling him to get access to hospital and gain moral, spiritual, and material supports from his social network